2001
DOI: 10.1890/0012-9658(2001)082[3479:tddrii]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity–disturbance Relationship: Is It Generally Strong and Peaked?

Abstract: The contemporary literature accepts that disturbance strongly influences patterns of species diversity, and that the relationship is peaked, with a maximum at intermediate levels of disturbance. We tested this hypothesis using a compilation of published species diversity–disturbance relationships that were gleaned from a literature search of papers published from 1985 through 1996 and from references therein. We identified 116 species richness–, 53 diversity–, and 28 evenness–disturbance relationships in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
261
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(297 citation statements)
references
References 29 publications
32
261
3
1
Order By: Relevance
“…Our observation that solid food introduction is followed by a purge in rare taxa is consistent with the idea that fewer species will persist in the face of intense disturbances [72]. In the 7-months infant, the genera that thrived in the milk-adapted microbiota - i. e. , Bifidobacterium and Bacteroides - continue to dominate, with the latter genus being now the most abundant in a majority of individuals.…”
Section: Resultssupporting
confidence: 86%
“…Our observation that solid food introduction is followed by a purge in rare taxa is consistent with the idea that fewer species will persist in the face of intense disturbances [72]. In the 7-months infant, the genera that thrived in the milk-adapted microbiota - i. e. , Bifidobacterium and Bacteroides - continue to dominate, with the latter genus being now the most abundant in a majority of individuals.…”
Section: Resultssupporting
confidence: 86%
“…Our experimental design involves multiple levels of disturbance (four levels of grazing intensity) and thus enables us to assess the validity of the intermediate disturbance hypothesis (the IDH), a classic ecological theory but associated with long-term debates (Mackey & Currie, 2001). The IDH predicts that communities under intermediate intensities or frequencies of disturbance should possess higher species diversity than that under low levels of disturbance or severe disturbance (Connell, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have refuted the idea of a positive relationship between disturbance and community diversity. A survey of empirical studies reported that non-significant relationships were the most common (Mackey and Currie, 2001), and a recent paper proposed, based on both empirical and theoretical grounds, that the IDH should be abandoned (Fox, 2013). For microorganisms, soil experiments showed that diversity declined with increasing disturbance frequencies, (Kim et al, 2013) and a negative diversity-disturbance relationship was also observed in natural marine sediments (Boer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%